The Application of Show and Tell (S&T) Methods in Teaching Vocabulary in Indonesian Junior Secondary School - Rahmaeni Rahmaeni (Majesty Journal, 2024)
The research aimed to find out the effectiveness of the show-and-tell method in boosting students’ vocabulary. The writer applied a quasi-experimental design with an experimental class and a controlled class. The populations of this research were the eight class students of SMP Negeri 7 Enrekang in the academic year 2023/2024 with a total number of 39 students. The sample of this research was VIII A (22 students) as experimental group and VIII B (17 students) as controlled group. It was taken by using a purposive sampling technique. This research applied the show-and-tell method in the experimental group and the problem-based learning method in the control group. The instruments of the research were pre-test and post-test which consisted of 25 numbers. The result of the data indicated that there was a significant difference between students’ post-tests in the experimental class and the controlled class The mean score of the post-test (91.45) in the experimental class was higher than the mean score of the post-test (76.94) in the controlled class. From the result of data analysis, it could be determined that the hypothesis was accepted. It revealed that the use of the show-and-tell method was effective in boosting students’ vocabulary mastery among the eighth-grade students of SMP Negeri 7 Enrekang. It is therefore, English teachers suggested applying the show-and-tell method in teaching the English process since it can make the English learning process more enjoyable, fun, and effective.